Docuseries y su aporte en el periodismo investigativo. Caso Netflix - Cabanilla Cadena, Dayana Roshel (2021)
This case study focused on the analysis of docuseries and how they contribute to investigative journalism. The importance of approaching this topic lies in how the nature of investigative journalism is shown through an audiovisual format that has become a phenomenon due to its great boom due to its sociocultural impact. The methodology used in this research for data collection is based on qualitative elements; the documentary review technique was applied and instruments such as: the observation sheet, discussion group and interviews with professionals specialized in the fields of film production and investigative journalism were used. Once the case study was concluded, it was possible to determine the contributions of docuseries in investigative journalism. Simultaneously, recommendations were obtained for the development of this type of productions by future communication professionals.